2022
DOI: 10.3390/life12101510
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Nomogram Based on High-b-Value Diffusion-Weighted Imaging for Distinguishing the Grade of Bladder Cancer

Abstract: Background: The aim was to evaluate the feasibility of radiomics features based on diffusion-weighted imaging (DWI) at high b-values for grading bladder cancer and to compare the possible advantages of high-b-value DWI over the standard b-value DWI. Methods: Seventy-four participants with bladder cancer were included in this study. DWI sequences using a 3 T MRI with b-values of 1000, 1700, and 3000 s/mm2 were acquired, and the corresponding ADC maps were generated, followed with feature extraction. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…A total of 1092 studies were initially identified through the literature search. After removing duplicates and screening for eligibility, 26 studies were finally included in the analysis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Figure 1 depicts the PRISMA flowchart.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 1092 studies were initially identified through the literature search. After removing duplicates and screening for eligibility, 26 studies were finally included in the analysis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Figure 1 depicts the PRISMA flowchart.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 26 eligible studies, 6 had the preoperative prediction of BCa pathological grade as their main objective, all of them dividing the data into low-grade and high-grade tumors [ 13 , 18 , 26 , 27 , 30 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Feng et al. ( 23 ) used a nomogram that combines radiomics features to predict the pathological grade of BCa. The AUC value of the ADC1700 model for differentiating low-grade BCa from high-grade BCa was 0.920 in the training cohort and 0.745 in the testing cohort.…”
Section: Discussionmentioning
confidence: 99%